288 Management of Lateral Third Clavicle Fractures: A Five-Year Review in a Regional Trauma Unit. (4th May 2021) - Hickland, P; Goodland, C; Zachariah, S; Murphy, L; Neil, M
Abstract: Introduction: Due to an increased risk of complications, lateral clavicle fractures are usually managed operatively. Unfortunately, there is no consensus on the optimal method of fixation. Method: We assessed practice in our regional trauma unit by retrospectively identifying patients who underwent fixation of a lateral clavicle fracture between 1 st August 2014 and 31 st July 2019. Data was extracted from electronic care records and imaging systems. Results: 44 patients were included, with the following demographics: mean age 26 years, 63.6% male, 65.9% high energy injury, and 68.2% Neer II fracture. The following operations were performed; hook plate fixation (HPF) = 10, locking plate fixation (LPF) = 16, coracoclavicular ligament reconstruction (CCLR) = 12, and LPF + CCLR = 6. Patients having LPF had a significantly larger post-operative coracoclavicular distance (7.6mm vs 13.5mm, p < 0.01), and a trend towards incomplete acromioclavicular joint reduction (50.0% vs 89.3%, p = 0.11). There was a significantly higher re-operation rate after HPF (100% vs 23.5%, p < 0.01). Conclusions: In our unit there is no favoured method of fixation of lateral clavicle fractures. When LPF is used, there should be consideration of concomitant CCLR. The high rate of re-operation after HPF must be considered.